VISUAL PERCEPTION OF PRIMARY DISPLAY PANEL OF COFFEE PACKAGING - Wirania Swasty; Arry Mustikawan; Fariha Eridani Naufalina (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2021)
Previous research only discussed the perception of color combinations for the primary display panel. This study is not only focused on color; but also on other visual elements. This research aims to know the primary display panel that is more desirable to consumers and uncover the linkage between product perception and preference by using quantitative approach. As for the method used is the case study of brand Puntang Coffee. Data collection was done by conducting literature study, redesign experiment and questionnaires, whereas data analyze by using the ANOVA test. From data, it was revealed that the highest valuation of respondents of all three designs displayed is design C; which proposed by the designer team, that are perceived better by respondents.